Antigone's sisters : on the matrix of love - Škof, Lenart, 1972- (Albany : State University of New York Press, 2021)
"An original and innovative exploration of Antigone, femininity, and love in various cosmological, philosophical, and theological contexts. In Antigone's Sisters, Lenart Skof explores the power of love in our world--stronger than violence and, ultimately, stronger even than death. Focusing on Antigone, Savitri, and Mary, the book offers an investigation into various goddesses and feminine figures from a variety of philosophical, mythological, theological, and literary contexts. The book also elaborates on the feminine aspects of selected concepts from modern philosophical texts, such as the Matrix in Jakob Böhme, Clara in F. W. J. Schelling, beyng in Martin Heidegger, chóra in Jacques Derrida, and breath in Luce Irigaray's thought. Drawing on Bracha M. Ettinger's concept of matrixiality, Skof proposes a new matrixial theory of philosophy, cosmology, and theology of love. Despite its many usages and appropriations, love remains a neglected topic within Western philosophy. With its new interpretation of Antigone and related readings of Irigaray, Kristeva, and Ettinger, Antigone's Sisters aims to identify some of the reasons for this forgetting of love, and to show that it is only love that can bring peace to our ethically disrupted world."--Publisher description
Prelude: The Matrix of Love / Ettingerian Matrixial Web -- Part 1: Cosmology / Theology of Love -- 1 Antigone / Savitri -- Antigone -- Savitri -- (Alcestis) -- 2 Metis / Lepa Vida -- The Tragic Death of Fair Vida and its Ethical Consequences -- Forgotten Layers of Ethics -- On Hospitality and Ethical Symptomatology -- (Favour) -- 3 Bethlehemite Concubine / Mary -- In Utero -- The Third Presence -- Toward a New Matrixial Theology of Incarnation -- (Sophia) -- Interlude: Interval / Time of Love -- Introduction -- Coming to the Stage of Ethics -- Constitution of the Other in Feuerbach, Chrétien, and Watsuji -- An Interval of Grace -- Part II: Philosophy / Ontology of Love -- 4 Clara / The Matrix -- Toward Schelling's Clara -- Schelling with Böhme: The Matrix -- Back to Schelling's Clara -- (Sister Angelica) -- 5 Beyng / Sister -- Toward the Ontology of Love: Ludwig Binswanger -- Forms of Pure Love: Parents and Children -- Love as Beyng's Sister -- Beyond the Margin: Beyng as a Plane of Love -- (Orin) -- 6 Irigaray / Breath -- Before Breath Is Born -- The Love of Breath -- Toward Sharing of the Divine Breath in Humans -- (Chóra) -- Postlude: Jesus / Antigone.
eBooks on EBSCOhost
Keywords: Antigone -- (Mythological character); Antigone -- (Mythological character); Femininity (Philosophy); Love; Love; Féminité (Philosophie); Amour; love (emotion); Ethics & Moral Philosophy; Religious; PHILOSOPHY; Philosophy; RELIGION; Theology; Gender Studies; SOCIAL SCIENCE; Femininity (Philosophy); Love